2014
DOI: 10.4244/eijv9i11a221
|View full text |Cite
|
Sign up to set email alerts
|

Doppler-based renal resistance index for the detection of acute kidney injury and the non-invasive evaluation of paravalvular aortic regurgitation after transcatheter aortic valve implantation

Abstract: Measurement of the Doppler-based RRI predicts risk for AKI and increased mortality rates at an early post-procedural time point and is related to the occurrence of more-than-mild paravalvular aortic regurgitation after TAVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…Of 273 articles identified by the initial search, 66 were retrieved for more detailed evaluation, and 24 trials were included in the study (Fig. ) . The characteristics of the included studies are reported in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 273 articles identified by the initial search, 66 were retrieved for more detailed evaluation, and 24 trials were included in the study (Fig. ) . The characteristics of the included studies are reported in Table .…”
Section: Resultsmentioning
confidence: 99%
“…AKI has emerged as an independent predictor of mortality after SAVR , but data concerning its impact on mortality after TAVI were not unique and conclusive with some studies indicating an increased mortality , while others showing no significant effects . In the study by Saia et al, the presence of AKI did not have an impact on 1‐year mortality, while only AKI 3 emerged as a significant predictor of it .…”
Section: Discussionmentioning
confidence: 98%
“…Meanwhile, Doppler-based RRI measurements can be useful in early AKI detection. Sinning et al proved that RRI was able to indicate AKI in the clinically crucial early hours immediately following the TAVR procedure, which was earlier than the rise in either creatinine or cystatin C 35. Although encouraging, both devices await their broad acceptance in everyday practice.…”
Section: Preventionmentioning
confidence: 99%
“…While the attempts to reduce stroke rates by TAVR embolic protection systems are promising ( 62 ), future studies on intervention or preventive measures to prevent renal emboli, especially in patients with CKD, are needed. Another intervention which requires further validation is the use of a Doppler-based renal resistance index to predict and identify patients at risk for AKI ( 63 ). In the future, progress in the research of urine biomarkers ( 64 ), electronic health records with an AKI alert ( 65 ) for early AKI detection, and risk stratification models will likely improve the renal outcomes of patients undergoing TAVR.…”
Section: Measures To Prevent Aki After Tavrmentioning
confidence: 99%